Ficothrips, a new genus of Thripinae Thysanoptera from Iran - Minaei, Kambiz (Zootaxa, 2012)
A new genus, Ficothrips gen. n., with one new species, F. moundi sp. n., is described from Fars province in south of Iran. Thesystematic position of this genus is discussed and its relationships to Scolothrips and Parascolothrips, two genera of leaf-living and predatory species.